Mind Map Students in Straight-Line Equations: Mistakes, Strenghts, and Weaknesses - Sumarsih Sumarsih (PAEDAGOGIA, 2019)
The study aims to find out the student's response about Mind Map, a student's fault in creating the Mind Map, the strengths and weaknesses of using Mind Mapping techniques in the learning of straight-line equations. Quantitative descriptive analysis of percentages was conducted against 84 responses to students about Mind Map, and evalua¬tive analysis was conducted against the Mind Map document by students of Grade VIII SMP Negeri 1 Masaran. Mistakes students include: coloring has not been made correctly, wrong in putting the next branch, making many branches of the main branch but not forwarded, the center of the Mind Map at the edges, wrong in dashing main idea with the idea Next branch, and did not write the idea on the next branch. The strenghts of using Mind Mappng techniques include: Students can make comparisons, learning time can be used more effectively, learning can be done continuously, provid¬ing a place to pour the next ideas, Students' creativity can be developed well, students become more actively asked, and students can make corrections to the truth of their answers. The weaknesses include: Mind Map function for benchmarking yet effective can be used, contrast difference cannot be found, and students' difficulty determines the main idea and the ideas of the branch.